Abdominal Actinomycosis Complicated with Hydronephrosis - 林建亨(Chien-Heng Lin); 陳安琪(An-Chyi Chen); 林曉娟(Hsiao-Chuan Lin); 林維卿(Wei-Ching Lin); 吳淑芬(Shu-Fen Wu) (Journal of the Formosan Medical Association, 2005)
Actinomycosis is a chronic supportive granulomatosis disease caused by the anaerobic Gram-positive organism Actinomyces. We report a 16-year-old boy with abdominal actinomycosis who presented with a 2-week history of intermittent abdominal pain. He complained of oliguria during the 3 days prior to admission. Abdominal computed tomography revealed a large inflammatory mass obstructing the ureter, which led to hydronephrosis of the right kidney. Exploratory laparotomy was performed and actinomycosis was confirmed by the presence of sulfur granules and filamentous bacteria. Postoperatively, the patient was successfully treated with long-term penicillin and recovered completely.